2009
DOI: 10.1186/bcr2239
|View full text |Cite
|
Sign up to set email alerts
|

FISH and immunohistochemical status of the hepatocyte growth factor receptor (c-Met) in 184 invasive breast tumors

Abstract: See related research by Götte et al., http://breast-cancer-research.com/content/9/1/R8 DIC = ductal infiltrating carcinoma; ER = estrogen receptor; FISH = fluorescent in situ hybridization; PR = progesterone receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 4 publications
6
16
2
Order By: Relevance
“…It is unclear what is causing this overexpression, a common cause is known to be gene amplification. Previous studies have failed to find MET amplification in breast cancer [20, 21]; the present study showed MET amplification in only 8% of the tumours of two cohorts, and amplification did not correlate with protein expression. Although protein expression did not correlate with poor prognosis, increased MET copy number tended in both cohorts to be indicative of a shortened distant and loco-regional recurrence-free survival.…”
Section: Discussioncontrasting
confidence: 87%
“…It is unclear what is causing this overexpression, a common cause is known to be gene amplification. Previous studies have failed to find MET amplification in breast cancer [20, 21]; the present study showed MET amplification in only 8% of the tumours of two cohorts, and amplification did not correlate with protein expression. Although protein expression did not correlate with poor prognosis, increased MET copy number tended in both cohorts to be indicative of a shortened distant and loco-regional recurrence-free survival.…”
Section: Discussioncontrasting
confidence: 87%
“…24 The expression rate of MET protein has been reported to vary from 15.0 to 72.7%. 34 This wide range in MET expression could primarily be the consequence of using different antibodies for immunohistochemical analysis and different threshold criteria for positivity (Supporting Information 5). SP44 monoclonal antibody (Ventana) showed clear membranous staining in positive cases without background staining.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, only a few small studies have compared IHC with FISH (Carracedo et al , 2009; Janjigian et al , 2011). In this study, we evaluated MET IHC and SISH concurrently in a large archival gastric cancer cohort.…”
Section: Discussionmentioning
confidence: 99%